Persepsi Masyarakat Asahan terhadap Penerapan Keadilan Restoratif dalam Perkara Pidana - Rahmat Suhargon (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The implementation of restorative justice is part of criminal law reform that emphasizes the restoration of social relationships among offenders, victims, and the community. This study aims to analyze public perceptions in Asahan Regency regarding the implementation of restorative justice in criminal cases and to explain the factors shaping its social legitimacy. This research employs a socio-legal method with a qualitative approach. Data were collected through semi-structured interviews with 10 informants consisting of 4 community members, 2 community leaders, 2 customary or religious leaders, and 2 law enforcement officials or individuals familiar with criminal law enforcement practices in Asahan Regency. The data were analyzed through data reduction, thematic data presentation, and inductive conclusion drawing. Data validity was tested through source triangulation and technique triangulation. The findings show that public perceptions of restorative justice in Asahan fall within a spectrum of acceptance and hesitation. Acceptance mainly occurs in minor and personal criminal cases, particularly when victims are involved, losses are restored, and offenders demonstrate responsibility. However, hesitation emerges due to the persistence of a retributive paradigm, low legal literacy, and concerns about inconsistent implementation by law enforcement officials. This study concludes that the social legitimacy of restorative justice in Asahan Regency is shaped by four main factors: legal literacy, consistency of law enforcement, victim and community participation, and compatibility with local cultural values. Thus, the effectiveness of restorative justice depends not only on formal regulation but also on social acceptance within the community.